Direct Costs of Bovine Spongiform Encephalopathy Control Measures in Germany. (10th January 2013) - Probst, C.; Gethmann, J. M.; Heuser, R.; Niemann, H.; Conraths, F. J.
Summary On 26 November 2000, the first autochthonous case of bovine spongiform encephalopathy (BSE) was detected in Germany. Since then, a total of 413 BSE cases have been confirmed, resulting in the culling and destruction of 17 313 heads of cattle. In view of the possible risks for human and animal health, Germany has adopted EU regulations along with some additional requirements concerning active surveillance and response measures after detecting a BSE‐positive animal. In this study, we used a stochastic model to estimate the costs incurred by the ensuing legislative amendments responding to BSE between November 2000 and December 2010. The total costs were estimated to range between 1847 and 2094 million Euros. They peaked in 2001 (about 394 million Euros) and declined since. About 54% of the costs (approximately 1000 million Euros) were incurred by the extension of the feed ban for animal protein to all farmed livestock. Active surveillance accounted for 21% (405 million Euros), the incineration of animal protein for 13% (249 million Euros) and the removal of specified risk material for 11% (225 million Euros). Only 1% of the costs was related to response measures after detecting a BSE‐positive animal, including indemnity payments for culled cattle and confiscated carcasses at the slaughterhouse.